Tributación en comercio electrónico en el Ecuador - Muñoz Guerrero, Diego Patricio (2013)
The problem with the lack of taxation within online trading has emerged due to the advances of technology and the emerging resonant presence of the internet. Through this media there has emerged an interchanging of goods and services, but because of the way in which these services are treated and processed, none of these transactions are generating tax. In addition, in Ecuador there currently does not exist any regulations which monitor commercial transactions that occur through the internet in regards to taxation